2006
DOI: 10.1007/s10562-006-0150-7
|View full text |Cite
|
Sign up to set email alerts
|

SAPO-11/HBeta composites for catalytic cracking of 2-butylene: effects of defect structure

Abstract: SAPO-11/HBeta composite was synthesized by using hydrothermal method (SB-H) and applied as catalyst for cracking of 2-butylene to C 2 -C 3 olefins. SB-H sample exhibited comparatively high selectivity and high yield of C 2 -C 3 olefins. XRD, IR, 27 Al and 31 P MAS NMR, Py-IR characterizations indicate that defect structure P(AlO 4 ) n (n < 4) really existed in SB-H sample. SAPO-11 and HBeta chemically bonded and the defect P(AlO 4 ) n (n < 4) formed during the hydrothermal synthesis of SB-H sample. P(AlO 4 ) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Up to now, different composite catalysts have been developed for various processes . Li et al synthesized HZSM‐5/MnAPO‐11 composite catalyst and concluded that the composite has a specific morphology with ZSM‐5 as core and MnAPO‐11 as shell .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, different composite catalysts have been developed for various processes . Li et al synthesized HZSM‐5/MnAPO‐11 composite catalyst and concluded that the composite has a specific morphology with ZSM‐5 as core and MnAPO‐11 as shell .…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, different composite catalysts have been developed for various processes. [31][32][33][34][35][36] Li et al synthesized HZSM-5/MnAPO-11 composite catalyst and concluded that the composite has a specific morphology with ZSM-5 as core and MnAPO-11 as shell. 36 In addition, results of the catalytic performance showed that HZSM-5/ MnAPO-11 composite catalyst has higher gasoline yield than ZSM-5.…”
Section: Introductionmentioning
confidence: 99%